Արևելյան ձեռագրագիտության կեղծարարական արվեստն ըստ Մատենադարանի հմր 137 ձեռագիր-օրինակի - Թաջարյան, Իվեթ Ն.; Ավետիսյան, Անի Ժ. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
In this article, we will discuss the Ms. № 137 from the Matenadaran's Arabic script collection. The manuscript was formerly in the main collection of the St. Etchmiadzin's Matenadaran on the basis of which the actual Matenadaran's Arabic script collection was formed. Initially, in the manuscript description lists of the Matenadaran this manuscript was mentioned as a work of Füzuli-Leyla and Majnun, and thus attributed to 18th century.
Keywords: Արևելագիտություն; Բանասիրություն; Պատմություն; Ձեռագրեր; Դրամագիտություն; Վիմագրություն